2017
DOI: 10.1016/j.physbeh.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolonged exposure to CO 2 on behaviour, hormone secretion and respiratory muscles in young female rats

Abstract: Atmospheric CO concentrations increased significantly over the last century and continuing increases are expected to have significant effects on current ecosystems. This study evaluated the behavioural and physiological (hormone status, muscle structure) effects of prolonged CO exposure in young female Wistar rats exposed at 700ppm of CO during 6h a day for 15days. Prolonged CO exposure, though not continuous, produced significant disturbances in behaviour with an increase in drinking, grooming and resting, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The rst questions was if breathing parameters showed any changes, as might be expected from an elevation in ambient CO2 levels. Others have reported potential stress after long repeated exposures to elevated CO2 in rats (700 ppm, 6hr/day over 15 days) 18 , whereas others have shown changes in minute volume associated with stressful procedures 32 . There were no signi cant changes to minute volume for any of the treated animals over the course of our studies, suggesting the treatments were reasonably tolerated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rst questions was if breathing parameters showed any changes, as might be expected from an elevation in ambient CO2 levels. Others have reported potential stress after long repeated exposures to elevated CO2 in rats (700 ppm, 6hr/day over 15 days) 18 , whereas others have shown changes in minute volume associated with stressful procedures 32 . There were no signi cant changes to minute volume for any of the treated animals over the course of our studies, suggesting the treatments were reasonably tolerated.…”
Section: Discussionmentioning
confidence: 98%
“…At present however these are the only studies we are aware of to address this issue in lung immunology. There have been several studies related to behavior 18 and at higher levels of CO2 where there is induction of hypercapnic acidosis in animals and cell cultures [19][20][21] . Results for these latter studies have been somewhat mixed, particularly in situations of LPS exposure versus more complex challenges such as tobacco extracts 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the highest value (4590 mg/m 3 ) measured at F2 exceeded neither the 8 h time weighted average (TWA) threshold of 9000 mg/m 3 (NIOSH, 1996;Department of Health and Human Services -NIOSH, 2007) nor the 15 min short-term exposure limit (STEL) of 54,000 mg/m 3 (NIOSH, 1996;Department of Health and Human Services -NIOSH, 2007). Nevertheless, a recent study by Martrette et al (2017) demonstrated that prolonged exposure to relatively low CO 2 doses (1260 mg/m 3 for 6 h a day for 15 days) can cause behavioral and physiological changes in mammals, affecting general behavior, hormonal status and myosin heavy chain (MHC) profile of diaphragm and oral respiratory muscles of young female rats. Noteworthy, CO 2 concentrations > 1260 mg/m 3 were occasional at F1 and frequent at F2.…”
Section: Fixed Measuring Stationsmentioning
confidence: 99%
“…Although the acute, toxic effects of exposure to very high levels of CO 2 (i.e., >100,000 ppm) are well known (Langford 2005;Scott et al 2009), the potential impacts of prolonged exposure to levels predicted by climate change models are vague. The sparse research in this broad area includes studies aimed at understanding the effects of exposure to elevated CO 2 in poorly ventilated classrooms/offices (Bakó-Biró et al 2012;Lu et al 2015;Muscatiello et al 2015), submarines (Rodeheffer et al 2018), and spacecraft (Law et al 2010;James et al 2011;Cronyn et al 2012;Hughson et al 2016) as well as small mammal laboratory studies aimed at understanding CO 2 -induced physiological changes (Schaefer 1982;Wade et al 2000;Kiray et al 2014;Martrette et al 2017). Many of these studies have been succinctly summarized in a recent review (Jacobson et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These previous studies show that exposure to CO 2 between 1,000 and 5,000 ppm for hours to months can result in a range of adverse health effects, including inflammation (Schneberger et al 2017; Thom et al 2017aThom et al , 2017b and cognitive impairment (Kajtár and Herczeg 2012;Satish et al 2012;Allen et al 2016;Snow et al 2019), with some effects manifesting after as little as a few hours of exposure. As the duration of exposure increases to weeks or months, kidney calcification, bone demineralization (Schaefer et al 1979;Schaefer 1982) and a range of behavioral changes have been measured (Kiray et al 2014;Martrette et al 2017).…”
Section: Introductionmentioning
confidence: 99%